Pengaruh Store Atmosphere, Kualitas Pelayanan, dan Kualitas Produk Terhadap Minat Beli Ulang : Studi Kasus di Kedai Kopi Berarti Solo Baru - Pramudya, Abdulrahman Rio; Walyoto, Sri (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2025)
This study aims to determine the influence of Store atmosphere, service quality and product quality on repurchase interest in Kopi Berarti in Solo Baru. The population in this study is the community in Sukoharjo Regency who are 20-50 years old. The sampling technique in this study uses non-probability sampling with the type of sampling used is pursposive sampling with a sample of 100 respondents. The variables used in this study consist of two types of variables, namely independent (X) and dependent variables (Y). The independent variables in this study are Store atmosphere, service quality and product quality. While the dependent variable used is Repurchase Interest. The data analysis method used is the multiple linear regression analysis method. Data processing uses the regretion. The results of the study showed that the variables of Store Atmosphere, Service Quality and Product Quality had a positive and significant effect on Repurchase Interest in Kopi Berarti in Solo Baru. the Adjusted R square value of 0.481 which means that Store Atmosphere, Service Quality, and Product Quality have an influence on repurchase interest of 48.1%. The remaining 51.9% was influenced by other variables.